Primary Sternal Osteomyelitis: A Case Report and Review. Issue 6 (12th June 2019) - Lopez, Christopher D.; Hill, J. Bradford; Stavropoulos, Christos; Lerman, Oren Z.
Abstract : Summary: Primary sternal osteomyelitis (PSO) remains a rare but morbid and challenging condition. Due to the limited reports of PSO in the literature, management of this disease continues to lack consensus. We present a case report highlighting how PSO remained, in our experience, refractory to medical management, and how operative intervention provided resolution, and a review of the literature.